Review and Survey of Methods for Analysis of Impurities in Hydrogen for Fuel Cell Vehicles According to ISO 14687:2019 - Beurey, Claire; Gozlan, Bruno; Carré, Martine; Bacquart, Thomas; Morris, Abigail; Moore, Niamh; Arrhenius, Karine; Meuzelaar, Heleen; Persijn, Stefan; Rojo, Andrés; Murugan, Arul (Frontiers in Energy Research, 2021)
Gaseous hydrogen for fuel cell electric vehicles must meet quality standards such as ISO 14687:2019 which contains maximal control thresholds for several impurities which could damage the fuel cells or the infrastructure. A review of analytical techniques for impurities analysis has already been carried out by Murugan et al. in 2014. Similarly, this document intends to review the sampling of hydrogen and the available analytical methods, together with a survey of laboratories performing the analysis of hydrogen about the techniques being used. Most impurities are addressed, however some of them are challenging, especially the halogenated compounds since only some halogenated compounds are covered, not all of them. The analysis of impurities following ISO 14687:2019 remains expensive and complex, enhancing the need for further research in this area. Novel and promising analyzers have been developed which need to be validated according to ISO 21087:2019 requirements.